THE STUDY OF NARRATIVE SEMIOTICS IN THE STORY OF ISRA MI’RAJ - Iwan Marwan; Wildan Taufiq (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2019)
The book of Bainama: Qishshah al-Mi'rȃj (BQM) by Imam Sheikh Najmuddin Al-Ghoithy Al-Dardiri, is an old literary works in the form of narrative prose (natsr qashashy). Therefore this research use the paradigm of A. J. Greimas that focused on how to sequence, and narrative aspects isotopy on the story of isra ' Ascension in the book "Bainama: Qishshah al-Mi'rȃj" by Imam Sheikh Najmuddin Al-Ghoithy Al-Dardiri. The results of this research found 8 or phase sequence IsraMi'raj story on the book of the BQM; This story includes the narrative aspect of the sender (Jibrl, Mikail, Izrail), objects (Isra Mi’raj), receiver (Prophet Muhammad), helper (Prophet Musa, Abu Bakr), subject (Prophet Muhammad), opposant (Jin Ifrit, Jews, Christians, Granny, Muth'im bin Abu Jahl, Ady); isotopes of enclosing space (House of the Prophet, wells, gardens, hills, madin, sky, Lake, hell, heaven) and time (night on the 27th of Rajab 10th year of Prophethood or year 1 SH coincide on February 26, 620-621 M, and by dawn on 27 10th Rajab prophetic or year 1 SH coincide on February 27, 620-621 M).Keywords: Narrative Semiotics, actan, isra mi’raj KAJIAN SEMIOTIKA NARATIF ATAS KISAH ISRA MI’RAJAbstrakKitab Bainama: Qishshah al-Mi’rȃj (BQM) karya Syekh Imam Najmuddin Al-Ghoithy Ad-Dardiri, merupakan sebuah karya sastra lama yang berbentuk prosa naratif (natsr qashashy). Oleh karena itu penelitian ini menggunakan paradigma A.J Greimas yang difokuskan pada bagaimana sekuen, aspek naratif dan isotopi pada kisah isra mi’raj dalam kitab “Bainama: Qishshah al-Mi’rȃj” karya Syekh Imam Najmuddin Al-Ghoithy Ad-Dardiri. Hasil Penelitian ini menemukan 8 fase atau sekuen kisah Isra Mi’raj pada kitab BQM; aspek naratif kisah ini meliputi sender (Jibril, Mikail, Izrail), objek (Isra Mi’raj), receiver (Nabi Muhammad saw), helper (Nabi Musa, Abu Bakar), subject (Nabi Muhammad saw), opposant (Jin Ifrit, Yahudi, Nasrani, nenek-nenek, Abu Jahal, Muth’im bin Ady); isotopi melingkupi ruang (rumah Rasulullah, sumur, kebun, bukit, madin, langit, telaga, neraka,surga) dan waktu (malam hari pada tanggal 27 Rajab tahun ke-10 kenabian atau tahun 1 SH bertepatan pada tanggal 26 Februari 620-621 M dan menjelang shubuh pada tanggal 27 Rajab tahun ke-10 kenabian atau tahun 1 SH bertepatan pada tanggal 27 Februari 620-621 M).Kata kunci: semiotika naratif, struktur aktan, Isra Mi’raj